Extrolites from non-aflatoxigenic Aspergillus flavus: potentials and challenges as emerging control strategy against Aspergillus flavus infection and aflatoxin contamination - Rahman, Mohd AH; Selamat, Jinap; Shaari, Khozirah; Ahmad, Syahida; Samsudin, Nik IP (Elsevier BV, 2024)
Mycotoxins are hazardous secondary metabolites produced by Aspergillus, Fusarium, and Penicillium, contaminating food and feed crops pre-, during, and post-harvest. Their consumption can lead to adverse health effects, impacting human health and agricultural productivity. Aflatoxins produced by members of Aspergillus section Flavi are the most toxically potent and naturally abundant mycotoxins. To mitigate mycotoxin contamination, physical, chemical, and biological methods have been developed and employed. Compared with laborious physical controls and hazardous chemical controls, biological controls offer a safer, cheaper, and more environmentally friendly alternative. The discovery of nonaflatoxigenic Aspergillus flavus strains has spurred biocontrol strategies to mitigate aflatoxin contamination in economically relevant crops. More recently, the focus has slightly shifted to the production of extrolites from nonaflatoxigenic A. flavus that could inhibit aflatoxigenic A. flavus growth and aflatoxin production. This review discusses the potentials and challenges of the emerging use of nonaflatoxigenic A. flavus extrolites as a biocontrol strategy.